Influence of Adolescents’ Smartphone Addiction on Mental and Emotional Development in West Java, Indonesia - Dhamayanti, Meita; Dwiwina, Resti Gradia; Adawiyah, Rubiah (Majalah Kedokteran Bandung, 2019)
Smartphone useis widespread globally, including in Indonesia. The excessive useand ubiquity of smartphone technology raise concerns on addiction and its effects on mental and emotional development ofadolescents. This study aimed to analyze the correlation between smartphone addiction and mental-emotional disorders inearly adolescents aged 11–12 years old in several primary schools in Bandung City and Sumedang District. This study was conducted October to December 2018 .Thiswas a cross-sectional study using convenient sampling technicwith unpaired categorical data for subject selection. Subjects were assessed with the Smartphone Addiction Scale Short Version (SAS-SV) and Strength and Difficulties Questionnaire (SDQ)which were self-administered by subjects. Subjects were classified into low level and high level smartphone user groups. Data were analyzed usingChi Square test. Out of 206 subjects, only 178 met the inclusion criteria with 44.9% (n=80) and 55.10% (n=98) were in  high- and low-level of smartphone addiction. The percentage of mental and emotional problems based on SDQ that was included in thenormal, borderline, and abnormal category was 60.7, 21.9, 17.4, respectively. Those with high-level smartphone addiction had mental and emotional problems with 1.425 prevalence ratio and CI95% 1.141–1.779. In conclusion, there is a correlation between smartphone addiction on mental and emotional problems of early adolescent.Key words: Early adolescent, mental and emotional, smartphone addiction, West Java, Indonesia Pengaruh Kecanduan Gawai pada Perkembangan Mental dan Emosional Remaja di Jawa Barat, IndonesiaPemakaian gawai sudah menyebar ke berbagai negara termasuk Indonesia. Pemakaian gawai sendiri memiliki dampak positif serta negatif. Salah satu dampak negatif yaitu mengalami kecanduan gawai sehingga mempengaruhi emosi dan perilaku dan juga dapat menurunkan produktifitas serta kualitas hidup. Tujuan penelitian ini adalah untuk menganalisis hubungan pengaruh kecanduan gawai terhadap gangguan mental emosional pada remaja awal usia 11 – 12 tahun. Metode penelitian analitik pontong lintang dilakukan pada subjek usia 11 – 12 tahun dari beberapa Sekolah Dasar Kota Bandung dan Kabupaten Sumedang pada Oktober sampai Desember 2018 . Subjek dipilih dengan metode convenient data kategori tidak berpasangan Subjek mengisi kuesioner yang berisi data sosiodemografi, Strength Difficulties Questionnaire (SDQ) dan Smartphone Addiction Scale – Short Version (SAS-SV). Subjek dibagi 2 kelompok tingkat kecanduan rendah dan tinggi. Data yang diperoleh dianalisis dengan menggunakan uji Chi Square. Dari 206 sebanyak 178 memenuhi kriteria. Subjek dengan tingkat kecanduan gawai tinggi sebanyak 80 (44,9%) dan rendah 98 (55,1%). Persentase gangguan mental emosional normal (60,7), borderline (21,9) dan abnormal (17,4). sebanyak 31 responden atau 17,4%. Terdapat hubungan bermakna Tingkat kecanduan gawai yang tinggi dan masalah mental emosi (rasio prevalens 1,45 (IK 1,141–1,779). Simpulan terdapat hubungan tingkat kecanduan gawai dan masalah mental emosio remaja awal usia 11 – 12 tahun.Kata kunci: Gawai, mental emosional, remaja awal